Molecular mechanisms controlled by mTOR in male reproductive system - Moreira, B (2019)
In recent years, the mammalian target of rapamycin (mTOR) has emerged as a master integrator of upstream inputs, such as amino acids, growth factors and insulin availability, energy status and many others. The integration of these signals promotes a response through several downstream effectors that regulate protein synthesis, glucose metabolism and cytoskeleton organization, among others. All these biological processes are essential for male fertility, thus it is not surprising that novel molecular mechanisms controlled by mTOR in the male reproductive tract have been described. Indeed, since the first clinical evidence showed that men taking rapamycin were infertile, several studies have evidenced distinct roles for mTOR in spermatogenesis. However, there is a lack of consensus whether mTOR inhibition, which remains the experimental approach that originates the majority of available data, has a negative or positive impact on male reproductive health. Herein we discuss the latest findings concerning mTOR activity in testes, particularly its role on spermatogonial stem cell (SSC) maintenance and differentiation, as well as in the physiology of Sertoli cells (SCs), responsible for blood–testis barrier maintenance/restructuring and the nutritional support of spermatogenesis. Taken together, these recent advances highlight a crucial role for mTOR in determining the male reproductive potential.